2019
DOI: 10.1111/jcmm.14332
|View full text |Cite
|
Sign up to set email alerts
|

Use of aspirin in the prevention of colorectal cancer through TIGIT‐CD155 pathway

Abstract: Colorectal cancer (CRC) is one of the most widespread malignant cancers, with a high incidence and mortality all over the world. Aspirin (ASA) otherwise known as acetylsalicylic acid, is a non‐steroidal anti‐inflammatory drug that has shown promising results in the prevention of chronic diseases, including several cancers. In previous studies, aspirin has been shown to reduce the incidence of CRC. Immune checkpoint blockade of T cell Ig and ITIM domain receptor (TIGIT) alone or combined with other immune check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…This is consistent with previous reports that non-steroidal anti-inflammatory drugs were effective in the treatment of inflammation in experimentally induced corneal alkali burns ( 46 – 48 ). Moreover, we found that ASA slightly inhibited the increase in AN-induced corneal epithelial cell proliferation, which is consistent with previous studies reporting that ASA inhibited proliferation and induced apoptosis in several types of human cells ( 49 , 50 ). Further in vivo studies investigating the effects of ASA and DNase I on corneal wound healing are necessary to develop new approaches for treating corneal alkali burns.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous reports that non-steroidal anti-inflammatory drugs were effective in the treatment of inflammation in experimentally induced corneal alkali burns ( 46 – 48 ). Moreover, we found that ASA slightly inhibited the increase in AN-induced corneal epithelial cell proliferation, which is consistent with previous studies reporting that ASA inhibited proliferation and induced apoptosis in several types of human cells ( 49 , 50 ). Further in vivo studies investigating the effects of ASA and DNase I on corneal wound healing are necessary to develop new approaches for treating corneal alkali burns.…”
Section: Discussionsupporting
confidence: 93%
“…As is well known that T4 could be catalyzed and transformed to T3, maybe liothyronine could block the TIGIT/PVR interaction and help to enhance the efficacy of ani-PD-1. It has been reported that aspirin could inhibit tumor cell growth by reducing the expression level of TIGIT, and that emodin could elicit the anti-tumor effects through downregulating the expression of PVR [ 39 , 40 ]. Quite different from that, liothyronine could exert anti-tumor effects by TIGIT/PVR blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous study, immunohistochemical staining of CRC cells and adjacent tissues have shown that TIGIT and CD155 are overexpressed in cancer cells' plasma membrane; however, CD226 was not expressed in colorectal cancer tissues. Furthermore, in this study, using western blot analysis in human colorectal cancer cell line (HT‐29), the TIGIT and CD155 upregulation has been proved 126 . Considering the extensive expression of TIGIT on both immune cells and CRC cells (human and murine), we believe that TIGIT has different functions.…”
Section: Tigit In Colorectal Cancermentioning
confidence: 61%